Ethical and evidential considerations on the use of novel therapies in veterinary practice. (4th March 2013) - Yeates, J.; Everitt, S.; Innes, J. F.; Day, M. J.
<x xml:space="preserve">Abstract</x> Novel therapies may be necessary both in the interests of the individual animal and in the advancement of veterinary science. However, special consideration is necessary to safeguard the welfare of the animals, ensure fully informed consent from the owner, determine the procedure's value in other cases and appropriately disseminate results. This article reviews ethical and evidential considerations raised when novel therapies are undertaken in veterinary practice, based on a series of committee meetings and intervening discussions held between members of the British Small Animal Veterinary Association Scientific Committee and Officers (2010–2011). The aim of this article is to encourage the advancement of novel veterinary therapies while safeguarding the welfare of animals.